2001
DOI: 10.1111/j.1559-1816.2001.tb02057.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotions in Comparative Negligence Judgments1

Abstract: This experiment studied the role of emotional arousal in mediating the impact of plaintiff and defendant blameworthiness and accident severity on comparative negligence judgments. Participants (N= 214) read descriptions and viewed photographs of 2 accident cases varying in outcome severity, victim blameworthiness, and defendant blameworthiness. Participants then rated their emotional responses to the cases, apportioned fault between the parties, and assessed gross and discounted damages. Blameworthiness and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…This result is consistent with legal instructions and outcome severity research (Feigenson et al, 1997(Feigenson et al, , 2001A.C. Smith & Greene, 2005;Wissler et al, 1997;Woody, 2008).…”
Section: Injury Severitysupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with legal instructions and outcome severity research (Feigenson et al, 1997(Feigenson et al, , 2001A.C. Smith & Greene, 2005;Wissler et al, 1997;Woody, 2008).…”
Section: Injury Severitysupporting
confidence: 91%
“…Unlike liability judgments, injury severity should influence compensatory damage awards -jurors should award larger sums of money to return more severely injured complainants back to their pre-injury state. Consistent with legal requirements, physical injury severity is often positively related to damage decisions (Feigenson, Park, & Salovey, 2001;Wissler, Evans, Hart, Morry, & Saks, 1997), exerting a stronger impact on damage than negligence decisions (Robbennolt, 2000).…”
Section: Outcome Severitymentioning
confidence: 89%
“…Although Feigenson et al (1997Feigenson et al ( , 1998 discuss their results in temis ofblaming the victim, the same cannot be said of the study reported here, given that the vignettes described the perpetrator alone and not the victim of the homicide. In the description of the arson, no mention is made of victims, although participants may have inferred that no one was hurt, given that the warehouse was described as "abandoned."…”
Section: Civil Liability and Ajfectmentioning
confidence: 53%
“…In a follow-up study, Feigenson et al (1998) found that anger, but not sympathy, toward the parties mediated the relationships between an accident's severity and a party's blameworthiness on mock jurors' determinations of fault. These findings are analogous to those reported here, in which anger.…”
Section: Civil Liability and Ajfectmentioning
confidence: 94%
“…Although researchers have recently shown an increased interest in the biasing role affective information has in legal decision‐making (see, generally, Bornstein & Wiener, ; as well as Feigenson, ; Feigenson, Park, & Salovey, ; Hastie, ), relatively few studies have tested interventions to correct for emotionally based bias in legal contexts. In one of these, Kramer, Kerr, and Carroll () tested three methods of countering the biasing impact of pre‐trial publicity: judicial instructions, deliberations, and a continuance.…”
Section: Introductionmentioning
confidence: 99%